KETERKAITAN KINERJA SOSIAL PERUSAHAAN DENGAN KINERJA KEUANGAN PERUSAHAAN - Ariyani, Vivi (Widya Warta, 2014)
This study aimed to examine and obtain empirical evidence of the relationship between corporate social performance and financial performance of companies in Indonesia. To get the sample, purposive sampling method was used. The number of the sample was 49 companies. While, the technique of data analysis made use of regression with SPSS program. To test the hypothesis, four equation methods were applied. The findings showed that financial performance of companies affected corporate social performance. In this case, the over resources enabled companies to invest the resources for sake of corporate social performance. Corporate social performance, on the other hand, did not affect financial performance of companies. This is apparently due to cultural differences of Indonesia and foreign countries which have been practicing social responsibility in each company.